Exploring Functional Impairment in Light of Prolonged Grief Disorder: A Prospective, Population-Based Cohort Study - Nielsen, Mette Kjaergaard; Christensen, Kaj Sparle; Neergaard, Mette Asbjoern; Bidstrup, Pernille Envold; Guldin, Mai-Britt (Frontiers in Psychiatry, 2020)
Background: Functional impairment is essential in the diagnostic criteria for prolonged grief disorder (PGD) in the ICD-11. It refers to the negative impact on everyday life, including inability to maintain the usual level of functioning. We aimed to assess the extent of functional impairment, emotion-related role limitation, and impaired social functioning before and after bereavement, and to explore associations with PGD, as measured by the 13-item Prolonged Grief Scale (PGDPG13). Method: Relatives of terminally ill patients (n = 1,622) completed a questionnaire before and after bereavement. The questionnaire assessed “overall functional impairment” (PG-13 item) and “aspects of functional impairment” measured by mean scores of the 36-item Short Form Survey (SF-36) subscales emotional role and social functioning (0: worst; 100: best). We analyzed associations between PGDPG13 and functional impairment prior to bereavement using logistic regression models adjusted for age, gender, personal relation, education, time interval to patient's death, and pre-loss grief. Results: In total, 51% reported overall functional impairment before bereavement, 27% reported functional impairment at 6 months after bereavement, and 19% reported functional impairment at 3 years after bereavement. The mean emotional role score was 47.5 (95%CI: 45.4–49.7) before bereavement, increasing to 77.4 (95%CI: 75.7–79.0) at 3 years after bereavement, compared to 85.1 (95%CI: 77.6–92.6) in a reference sample. Mean social functioning score increased gradually reaching the mean of the reference sample at 3 years after bereavement. PGDPG13 was present in 26% of those with overall functional impairment at 6 months after bereavement, decreasing to 11% at 3 years after bereavement. Pre-bereavement measures of emotional role and social functioning were associated with PGDPG13at 6 months and 3 years after bereavement. Discussion: Overall functional impairment was prevalent as reflected in low scores on daily activities and social functioning compared to a reference sample. Functioning may be an important factor during caregiving and bereavement and pre-bereavement functional impairment was associated with PGDPG13. Future studies should investigate if maintaining daily activities and social functioning before bereavement could be key in early supportive care. Moreover, the role of functional impairment in bereavement interventions should be explored.